IMPLEMENTASI PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN SAK EMKM PADA UMKM PASTELLIA INTERMODA BUMI SERPONG DAMAI DENGAN MENGGUNAKAN APLIKASI SI APIK PERIODE 2018 – 2019 - Bettynia Dwi Orparani; Yumniati Agustina (Jurnal Ilmiah Akuntansi Rahmaniyah, 2021)
The purpose of this study is to evaluate whether the financial statements based on SAK EMKM have been applied by Pastellia Intermoda Bumi Serpong Damai SMEs, compare the financial statements of Pastellia Intermoda Bumi Serpong Damai SMEs with Si Apik's version of the financial statements, and interpret the results of a comparative analysis which is then drawn into a conclusion. . This research method is a comparative & descriptive method. Data obtained through interviews, observation. Comparative analysis of the data by analyzing the presentation of the financial statements of Pastellia Intermoda Bumi Serpong Damai SMEs with a theory that refers to the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) and comparing financial statements manually with financial reports using the Si Apik application. The results of this study are that the types of financial statements produced are statement of financial position (balance sheet), income statement and cash flow statement, and do not make notes on financial statements (CALK) so that they are not in accordance with SAK EMKM. The difference between the financial statements produced by Pastellia Intermoda Bumi Serpong SMEs and the Si Apik application is in the statement of financial position and income statement related to depreciation of fixed assets